Current status of antigen-specific T-cell immunotherapy for advanced renal-cell carcinoma. Issue 7 (3rd July 2021) - Xu, Yuexin; Miller, Chris P.; Warren, Edus H.; Tykodi, Scott S.
ABSTRACT: In renal-cell carcinoma (RCC), tumor-reactive T-cell responses can occur spontaneously or in response to systemic immunotherapy with cytokines and immune checkpoint inhibitors. Cancer vaccines and engineered T-cell therapies are designed to selectively augment tumor antigen-specific CD8 + T-cell responses with the goal to elicit tumor regression and avoid toxicities associated with nonspecific immunotherapies. In this review, we provide an overview of the central role of T-cell immunity in the treatment of advanced RCC. Clinical outcomes for antigen-targeted vaccines or other T-cell-engaging therapies for RCC are summarized and evaluated, and emerging new strategies to enhance the effectiveness of antigen-specific therapy for RCC are discussed.